STUDY OF THYROID PROFILE IN GERIATRIC TYPE-2 DIABETICS IN JHARKHAND - Jha, Pankaj Kumar; Mandal, Gunjan Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To study the association of the two endocrinal disorders (Diabetes mellitus and thyroid disease) in randomly selected geriatric patients. Method: The study includes 80 patients in geriatric age groups with type 2 diabetes mellitus visiting the Medicine out patients department. Thyroid profile were assayed in type 2 diabetic patients. Results: It was noted that thyroid dysfunction was prevalent in 41(51.25%) out of the 80 geriatric age group patients with 31(38.75%) being hypothyroidism, 7 (8.7%) having subclinical hypothyroidism and 3 (3.7%) having a hyperthyroid state. Conclusion: The study shows that screening should be strongly recommended for all type 2 diabetics to rule out thyroid dysfunction in patients with increasing age. Keywords: Thyroid profile, Geriatric patients, Diabetes mellitus.